The Tourette syndrome & OCD checklist : a practical reference for parents and teachers - Conners, Susan, 1948- (San Francisco, CA : Jossey-Bass, 2011)
'Up-to-date, reliable information about Tourette Syndrome and related disorders for teachers and parents. Children with TS are often teased and punished for the unusual yet uncontrollable symptoms of their disorder. Academic failure is common. The Tourette Syndrome/OCD Checklist helps parents and teachers to better understand children and youth with TS and/or OCD and provide the support and interventions these children need. Presented in a simple, concise, easy-to-read checklist format, the book is packed with the latest research, practical advice, and information on a wide range of topics. Provides a wealth of information on Tourette Syndrome, Obsessive-Compulsive Disorder, and related conditions Includes strategies for discipline and behavior management, advice on supporting and motivating kids with TS and OCD, homework tips, and more Shows how to educate peer students about TS and OCD Loaded with practical information, strategies, and resources, this book helps parents and teachers to better understand Tourette Syndrome and OCD and shows how every individual can reach their potential in school and in life'--
Includes bibliographical references and index.
Keywords: Tourette syndrome in children; Obsessive-compulsive disorder in children